Pengaruh Pembinaan Ekstrakurikuler terhadap Prestasi Belajar Siswa di SMA IT Miftahulhuda - hardianti, Dian; Muslih, Yuyun Nuriyah (An-Nahdliyyah: Jurnal Studi Keislaman, 2024)
Extracurricular coaching has an important role in helping students develop their potential, interests and talents so that they can play a more active role in the learning process and then ultimately influence their learning achievement. Through targeted coaching, we can create and develop superior and quality Human Resources. So, the aim of this research is to determine the magnitude of the influence of extracurricular coaching on student learning achievement at Miftahulhuda IT High School. The research method used is a descriptive method with a quantitative approach. The number of samples used was 30 respondents. The data collection technique uses a questionnaire and is processed using the Regression Test and Determination coefficient analysis techniques. The results of the research show that there is a positive influence and relationship from variable 0.001 < 0.05, so the alternative hypothesis H0 is rejected and Ha is accepted. The calculation results for the coefficient of determination are (0.638) or 63%. This means that extracurricular coaching contributes 63% to learning achievement.